2018
DOI: 10.1136/bmjopen-2018-021552
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and spectrum of tornado injury and its geographical information system distribution in Yancheng, China: a cross-sectional study

Abstract: ObjectivesFew studies of tornado injuries have considered differences related to damage levels and Enhanced-Fujita (EF) scale ratings. This study aimed to evaluate the pattern, spectrum and geographical distribution of injuries related to the Yancheng tornado and provide guidelines for effective emergency medical strategies.SettingThe study was conducted at three hospitals which treated patients with injuries related to the tornado in Yancheng, China.ParticipantsWe obtained the records of 451 patients with tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…We have conducted our simulations with respect to different distributions of AIS grades reported in the literature. In addition to the distribution for victims of motor vehicles accidents, reported by Baker et al [ 1 ] and reproduced in Table 1 , we consider the distributions of AIS grades for 174 adult victims of fall accidents reported by Lopes et al in [ 21 ], 451 patients with tornado-related injuries reported by Deng et al in [ 22 ] 2 , and 278 victims of traumatic maternal injuries reported by Awoleke et al in [ 23 ]. The details of each distribution are reproduced in Table 10 and the code in Appendix A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have conducted our simulations with respect to different distributions of AIS grades reported in the literature. In addition to the distribution for victims of motor vehicles accidents, reported by Baker et al [ 1 ] and reproduced in Table 1 , we consider the distributions of AIS grades for 174 adult victims of fall accidents reported by Lopes et al in [ 21 ], 451 patients with tornado-related injuries reported by Deng et al in [ 22 ] 2 , and 278 victims of traumatic maternal injuries reported by Awoleke et al in [ 23 ]. The details of each distribution are reproduced in Table 10 and the code in Appendix A .…”
Section: Resultsmentioning
confidence: 99%
“…The data used in the current study are available in references [ 1 ], [ 21 ], [ 22 ], and [ 23 ]. The source code for the queuing simulation is provided in the R language, in Appendix A .…”
mentioning
confidence: 99%
“…The severity of the tornado caused a large number of tornado-related deaths in China. 5,6 After the tornado, a large number of patients were sent to the hospital within a short period of time, placing great demands on medical resources. Injuries to the thorax during the tornado were common and presented a major challenge to the emergency medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 29,371 houses, 2 primary schools, and 8 factories were damaged; more than 50,000 people were directly affected by the tornado [4]. This tornado was one of the largest disasters in recent decades in Jiangsu Province, and the deadliest tornado in China in nearly half a century [2, 5]. In the afternoon on August 11, 2017, a Fujita 3 (F-3, which is similar to EF-3) [6] tornado hit Keshiketeng County and Wengniute County in Chifeng City, Inner Mongolia (Fig.…”
Section: Introductionmentioning
confidence: 99%